2017
DOI: 10.3847/1538-4357/835/2/210
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Gradient Study of Interstellar Medium Turbulence Using the Canadian Galactic Plane Survey

Abstract: We have investigated the magneto-ionic turbulence in the interstellar medium through spatial gradients of the complex radio polarization vector in the Canadian Galactic Plane Survey (CGPS). The CGPS data cover 1300 square-degrees, over the range 53 • ≤ ≤ 192 • , −3 • ≤ b ≤ 5 • with an extension to b = 17.5 • in the range 101 • ≤ ≤ 116 • , and arcminute resolution at 1420 MHz. Previous studies found a correlation between the skewness and kurtosis of the polarization gradient and the Mach number of the turbulenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Each simulation is assigned a code of the form Ms0.8Ma1.7, for example, which means that the simu- The mean magnetic field is in the x direction, and we view the cube along the x, y, or z directions, where the latter is shown above. The inset image shows polarization gradients from the Canadian Galactic Plane Survey (see Herron et al 2017c), where black denotes a large amplitude of the polarization gradient, and white denotes a small amplitude.…”
Section: Magnetohydrodynamic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each simulation is assigned a code of the form Ms0.8Ma1.7, for example, which means that the simu- The mean magnetic field is in the x direction, and we view the cube along the x, y, or z directions, where the latter is shown above. The inset image shows polarization gradients from the Canadian Galactic Plane Survey (see Herron et al 2017c), where black denotes a large amplitude of the polarization gradient, and white denotes a small amplitude.…”
Section: Magnetohydrodynamic Simulationsmentioning
confidence: 99%
“…Gaensler et al (2011) found that the polarization gradient traces spatial variations in the magnetoionic medium, and Burkhart et al (2012) found that statistics of the polarization gradient, such as the skewness and genus, were sensitive to the sonic Mach number of their simulations. However, Herron et al (2017c) cast doubt on the ability of the skewness of the polarization gradient to probe the regime of turbulence, as they found that the skewness of the gradient was very sensitive to angular resolution, and the size of the evaluation box used to calculate the skewness, in the Canadian Galactic Plane Survey dataset (CGPS, Landecker et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This has previously been applied to limited areas (e.g. Gaensler et al 2011;Herron et al 2017), but the area, sensitivity, and resolution of S-PASS render it possible to construct an image of turbulence throughout the Milky Way (Iacobelli et al 2014;Robitaille et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The path in the image plane corresponds to a path in the Q-U plane, and we calculate the speed at which we traverse this path. The background image is of polarization gradients from a portion of the Canadian Galactic Plane Survey, see Herron et al (2017) for more information.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Burkhart et al (2012) calculated the amplitude of the polarization gradient for mock observations of synchrotron emission propagating through a turbulent magnetoionic medium, and found that statistics of polarization gradient structures, such as the genus, were sensitive to the regime of turbulence. The polarization gradient has been applied to observations by Iacobelli et al (2014), Sun et al (2014) and Herron et al (2017), to constrain the sonic Mach number of observed magnetoionic turbulence, and Robitaille & Scaife (2015) found that there were different networks of filaments in the images of the amplitude of the polarization gradient on different angular scales in a field of the Canadian Galactic Plane Survey (Landecker et al 2010). Robitaille et al (2017) also compared the polarization gradient to the E-and B-modes (Zaldarriaga & Seljak 1997) of diffuse synchrotron emission in the S-band Polarization All Sky Survey (Carretti 2010;Carretti et al 2013), and found that the two had similar properties, and provide complementary information on observed magnetoionic turbulence.…”
Section: Introductionmentioning
confidence: 99%